You can relax and overcome stress : Change Your Thinking, Change Your Life - George, Mike, (Watkins Publishing, 2014)
With 25 simple mental and physical exercises, this book will show you how to understand and control your personal stress triggers by using simple techniques such as breathing, visualization, mediation, sleep enrichment and physical exercise to help you relax and unwind.